Tree‑ring records of snow‑avalanche activity in the Rodna Mountains (Eastern Carpathians, Romania) - Kholiavchuk, Dariia; Gavrilă, Ionela Georgiana; Holobâcă, Iulian Horea; Ridush, Oles; Ridush, Bogdan; Pop, Olimpiu; Meseşan, Flaviu (Natural Hazards, 2022)
We reconstruct snow-avalanche (SA) activity along three adjacent avalanche paths in the northern part of the Rodna Mountains (Eastern Carpathians, Romania) using tree-ring analyses. We sampled a total of 238 disturbed Norway spruce (Picea abies (L.) Karst.) trees and used the growth anomalies found in tree rings to obtain an avalanche chronology at the subregional scale spanning the 1979–2019 period. Multiple regression analysis of weather data covering the tree-ring-based reconstructed avalanche winters provided three distinct synoptic patterns favoring SA activity: (i) in January, when destabilization of the snow cover occurs during warm periods; (ii) in April, when destabilization of the snow cover is due to the combined efect caused by the warm days and the ones with heavy rainfall; and (iii) in November, during cold periods with snowfalls and strong winds. This study based on the tree-ring approach coupled with multiple regression analysis contributes to a better understanding of the snow-avalanche regime at both local and subregional scale. It also provides the basis for further research to decipher the linkage between the synoptic conditions favoring the naturally released avalanches at a regional scale
Keywords: Snow avalanches · Tree-ring reconstruction · Multiple regression · Rodna Mountains (Eastern Carpathians)